Akuntabilitas Sebagai Prinsip Pengelolaan Keuangan Lembaga Pendidikan - Bagus Setiawan; Shaleh, Shaleh (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to find out about the importance of accountability as a principle in the financial management of educational institutions. As for this research, the method used is a non-research method, namely using literature or library research, by collecting some information from various sources such as journals, proceedings, or examination of online literature. The results of this study indicate that accountability is an effort that must be made by an institution in being accountable for activities or reporting in detail and systematically to certain parties. This also applies to educational institutions, accountability is needed as a form of reporting, especially accountability in the financial management of educational institutions. Parties responsible for managing educational institutions' finances must be able to account for and report financial conditions in detail to certain parties, especially education customers. The financial management of educational institutions must be carried out regularly so that they can be utilized and allocated according to the needs of the school. with clear financial accountability of educational institutions, a sense of trust will grow automatically by educating customers